Click, Clack, Quackity-Quack: An Alphabetical Adventure - Cronin, Doreen; Lewin, Betsy (New York : Atheneum Books for Young Readers, 2006)
An assortment of animals gathers for a picnic.
Reprint. Originally published: 2005.
Keywords: Picnicking -- Fiction; Animals -- Fiction; Alphabet